KOMPONEN MANAJEMEN JASA TERPADU TERHADAP KEPUASAN NASABAH TABUNGAN PADA PT. BANK DANAMON INDONESIA, TB CABANG MESJID LAMA PALEMBANG - Nelly Nelly (Universitas Indo Global Mandiri)
The study aimed to determine the components of integrated management services simultaneously and partially on customer satisfaction savings in PT Bank Danamon Indonesia, Tbk Palembang branch of the Mesjid Lama and to know the components of an integrated service management is a dominant influence on customer satisfaction savings. The study was conducted on customers of Bank Danamon branches of the Mesjid Lama special BDI Palembang active customers savings of up Desember 2015 as many as 93 customers using purposive sampling method. Data analysis techniques used were Linear Multiple Regression analysis. Test result show that components of integrated management services at the same cost savings affect customer satisfaction. Components of intergrated management service consisting of processes, productivity and quaility, promotion and education, physical evidence as well as pricing and other service costs a significant partial effect on customer satisfaction while saving variable products, places and other times, people do not have a significant partial savings in customer satisfaction. Components of physical evidence is the dominant factor affecting customer satisfaction savingsKeyword : Integrated Service Management Component, Customer Satisfaction